Analisa Kebutuhan Ahli Teknologi Laboratorium Medik Berdasarkan Beban Kerja di Puskesmas Sentosa Baru - Cindy Salsabila (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
Abstract: Background: Primary Health Care is a technical implementing unit (UPT) from the district or city health office which has responsibility for administering individual health units (UKP) and public health units (UKM). Health providers at puskesmas prioritize and prioritize promotive and preventive efforts in their working areas. Medical Laboratory Technologist (ATLM) is one type of health worker in Law Number 36 of 2014 concerning Health Workers. Goals : The purpose of the study was to see how adequate the needs of health workers are, especially the fulfillment of medical laboratory experts at the Sentosa Baru Health Center by using the workload method. Methods : This study uses a qualitative method through interviews. The sample/respondents of the study were ATLM institutions at the Sentosa Baru Health Center with a population of the Sentosa Baru Health Center. Data were collected in primary and secondary forms. Results : Based on the findings in the study, ATLM at the Sentosa Baru Health Center has a working time of 37.5 hours/week so that for 1 working day the ATLM is 6.25 hours or rounded up to 6 hours/day. With a total of 2 ATLM employees. Conclusion : The need for medical laboratory experts at the Sentosa Baru Health Center is ideal and the proportion of types of work is good. This is in accordance with the Regulation of the Minister of Health of the Republic of Indonesia No. 37 of 2012 concerning the Organization of the Central Public Health Laboratory.